An intensive and collective style of farm work that enables the agroecological transition: A case study of six French farm machinery cooperatives - Lucas, Véronique; Gasselin, Pierre (Frontiers in Sustainable Food Systems, 2022)
The higher intensity of labor observed in many agroecological farming systems has been little studied by the scientific community, especially in terms of work organization. Narrative interview research concerning 34 farmers in six French farm machinery cooperatives, on the basis of the farming styles framework, allows us to highlight a specific style of farm work conducive to the agroecological transition. Farmers members of these cooperatives have developed a long-standing reliance on peer-to-peer cooperation, gradually shaping a labor-intensive and collective style of farm work to make their conventional farming systems viable. They have then remobilized with relative ease the structuring basis of their initial organization of work, i.e., labor intensity and peer-to-peer cooperation, to develop agroecological practices.